THE INVESTIGATION - ACTION FOR INNOVATION OF THE EDUCATIVE TASK - Gómez Gallardo, Luz Marina (2014)
The present article is structured according to two transcendental subjects for the Education in Peru: One is the approach of the investigation-action within the framework of the theories about the practice of the educational function, and the other is the investigation-action as a strategy of learning in the formation of the teaching staff. The investigation process-action constitutes a continuous process, a spiral, in which the moments of problem, diagnosis, design of a change proposal, application of the proposal and evaluation take place, to reinitiate a new circuit beginning with a new problematic situation. This type of investigation acquires a great importance in our educative field because it helps to surpass the binomials of theory-practice; educator-investigator; and thus it makes possible to unify theory and practice. In such sense, it is necessary that the educational investigation counts with suitable strategies, that will allow it to further deepen their formation about the investigation of the events of their partner-cultural surroundings